Parents' Stress and Children's Psychological Problems in Families Facing the COVID-19 Outbreak in Italy - Spinelli, Maria; Lionetti, Francesca; Pastore, Massimiliano; Fasolo, Mirco (Frontiers in Psychology, 2020)
Objectives. The present study aimed to explore the effect of risk factors associated with the COVID-19 outbreak experience on parents and children well-being. Methods. Parents of 2 to14 years old children completed an on-line survey reporting their home environment condition, the contact they had with the pandemic consequences, the difficulties experienced due to the quarantine, their perception of individual and parent-child dyadic stress, and children emotional and behavioral problems. Results. Results evidenced that the perception of the strain of the quarantine is a crucial factor that undermines both parents and children well-being. Quarantine’s impact on children’s behavioral and emotional problems is mediated by parent’s individual and dyadic stress with a stronger effect of the latter. Parents who reported more difficulties in dealing with quarantine show more stress. This, in turn, increases children problems. Living in a more at-risk area, the quality of home environment, or the contact with the pandemic consequences, do not have effect on families’ well-being. Conclusions. Dealing with quarantine is a particularly stressful experience for parents who must balance personal life, work, and children upbringing, being left alone without other helping sources. This situation puts parents at a higher risk of experiencing distress, potentially impairing their ability to be supportive caregivers. The lack of support these children receive in such a difficult moment may be the reason of their higher psychological symptoms. Policies should take more into consideration the implications of the lockdown for families’ mental health, and supportive intervention for the immediate and the future should be promoted.